Density dependence of SOL power width in ASDEX upgrade L-Mode. (August 2017) - Sieglin, B.; Eich, T.; Faitsch, M.; Herrmann, A.; Nille, D.; Scarabosio, A.; Upgrade Team, ASDEX
Highlights: The power spreading in the divertor region is described by the competition of perpendicular heat diffusion and parallel electron conduction. The in/out asymmetry of the power fall-off length λq is studied for a closed divertor configuration in hydrogen, deuterium and helium. A strong density dependence of λ q, i on the inner divertor target with density is observed. An interpretation of the observed dependencies of λq using a drift based model is given. Abstract: Understanding the heat transport in the scrape-off layer (SOL) and the divertor region is essential for the design of large fusion devices such as ITER and DEMO. Current scalings for the power fall-off length λq in H-Mode [1] are available only for the outer divertor target at low densities with low recycling divertor conditions. For the divertor power spreading S only an empirical scaling for ASDEX Upgrade L-Mode is available based on global plasma parameters [2]. Modelling using SOLPS shows a dependence of S on the divertor electron temperature [3]. A more detailed analysis of the heat transport forming λq and S is presented for ASDEX Upgrade L-Mode discharges in hydrogen (H), deuterium (D) and helium (He). For low densities the power fall-off length λ q, o on the outer divertor target in H and D is described by the same parametric dependencies as the H-Mode scaling[1] but with a larger absolute size of the power fall-off length in L-Mode. The divertor power spreading S is studied using the local divertor measurements of the target electron temperature T e, tar and density n e, tar . It is found that the competition of the diffusive transport parallel and perpendicular to the magnetic field forming S ∝ χ ⊥ / χ ∥ is dominated by the temperature dependence of parallel electron conduction. For high divertor temperatures the ion gyro radius has a significant contribution to S, resulting in a minimum of S at ∼30 eV. A recent study [4] with an open divertor configuration found an asymmetry of the power fall-off length between inner and outer target with a smaller power fall-off length λ q, i on the inner divertor target. Measurements with a closed divertor configuration find a similar asymmetry for low recycling divertor conditions. It is found, in the experiment, that the in/out asymmetry λ q, i / λ q, o is strongly increasing with increasing density. Most notably the heat flux density at the inner divertor target is reducing with increasing λ q, i whilst the total power onto each divertor target stays constant. It is found that λ q, o exhibits no significant density dependence for hydrogen and deuterium but increases with about the square root of the electron density for helium. The difference between H, D and He could be due to the different recycling behaviour in the divertor. These findings may help current modelling attempts to parametrize the density dependence of the widening of the power channel and thus allow for detailed comparison to both divertor effects like recycling or increased upstream SOL cross field transport.